THE EFFECT OF METACOGNITVE LEARNING STRATEGY TOWARDSTUDENTS’ ACHIEVEMENT IN LISTENING COMPREHENSION (AN EXPERIMENTAL STUDY AT THE SECOND YEAR STUDENTS OF MTs.AL- MADANIYAH JEMPONG MATARAM IN ACADEMIC YEAR 2016-2017 - Hidayati Hidayati (Linguistics and ELT Journal, 2017)
This study is about the effect of metacognitive learning strategy toward students’ achievement in listening comprehension an experimental study at the second-year students of MTs.AL-MADANIYAH Jempong Mataram in the academic year 2016-2017. The purpose of the study is to know whether there is an effect of metacognitive learning strategy or not toward students’ achievement in listening comprehension. The research method was quasi-experimental research with nonequivalent control group design. The population of the research was all of the second year Students of MTs.AL-MADANIYAH Jempong Mataram, conducted of two classes as a sample; Experimental group II A and Control group II B. II A was taught by using Metacognitive Learning Strategy while II B was taught without using Metacognitive Learning Strategy. The researcher gave the Listening test to gather the data. The formula that used to analyze the data was t-test. It is supposed to know the significant difference between students’ score in the experimental group and control group. Based on the computation of the t-test formula, it was found that the mean score of the experimental group was 17,6 and the mean score of the control group was 9,2. After analyzing the data, it was found that t-test was 5,626. The degree of freedom (df) was (Nx+Ny-2) = (25+25-2) =48. The degree of freedom from 38 students as the sample. The researcher got a score for confident level 0.5 or 95% and score 2.000, for confident level 0.1 or 99% is 2.660. It means that t-test was higher than t-table. After the data had been obtained; it was found that metacognitive learning strategy has a positive effect on teaching listening. It showed by the significant value of t-test >t-table. It means that Ha (alternative hypotheses) was accepted because t-test was higher than t-table. Based on the explanation, the researcher concludes that the effect of metacognitive learning strategy toward students achievement in listening comprehension at the second year students of MTs.AL- MADANIYAH Jempong Mataram has a positive effect.